ANALISIS QUALITY CONTROL MUTU MINYAK KELAPA SAWIT DI PT. PERKEBUNAN LEMBAH BHAKTI ACEH SINGKIL - Yulianto (AMINA, 2019)
This study aims to determine the analysis of the quality control of palm oil quality in PT. Lembah Bhakti Aceh Singkil Plantation. The function of implementing quality control is to control the quality of the initial input in the form of completion of raw materials, the production process, to the process of output of finished goods. This study uses several methods, namely filtration and titration. The average quality of palm oil at FFA levels ranges from 3.39 to 4.97 with a max.3 standard, a moisture content ranging from 0.12 to 0.3% with a max standard. 0.2%, and impurities levels ranged from 0.015-0.025% with the max standard. 0.02%. Based on the results of the study it can be concluded that the measurement of quality control that is carried out is very influential in product quality, so that it can affect the income. Where the income of a company depends on the CPO oil selling price in PMKS PT. Perkebunan Lembah Bhakti. The selling value in marketing is very dependent on the quality of the CPO.